The study of technogenically transformed water ecosystems within аviation facilities operation area - Madzhd, Svitlana; Pysanko, Yana (My University, 2018)
The object of the research is technogenically transformed aquatic ecosystem which helps to develop water protection measures and ensure the ecological safety of technogenically conditioned ecosystems of rivers passing through urban areas within aviation repair facilities. The conceptual model of aquatic ecosystem consists of the Nyvka and Irpin rivers, both aquatic ecosystems belong to the Dnieper basin, and the permanent trophic connection makes it possible to consider them as the conceptual majority of interconnected constituents. The aim of the work: to study main features of the formation of technogenically conditioned water ecosystems of small and medium rivers due to anthropogenic influence of the aviation repair facilities. Methods: were used a biotesting method, a method of the complex water quality assessment, a substrate biological transformation model based on the law of non-linear mathematical model of Mono and Michaelis-Menten. The technogenic impact index for every pollutant was calculated. Results: it was found the content of heavy metals, oil products, nitrogen, nitrite nitrogen, nitrate nitrogen in the surfacewater of the Nyvka and Irpin rivers. Investigated samples of the Nyvka water were of V water quality class and the Irpin water was of I V water quality class. The hydrochemical analyze of the Irpin river has shown that limitation factors affecting the water quality, cause the disturbance of the self-remediation ability of the water ecosystem. Was shown changes of contaminant concentration in the Irpin River current. Discussions: obtained results of the modeling of the Irpin water self-remediation from contaminants are represented that the constant for contamination agents such as nitrogen, nitrite nitrogen, nitrate nitrogen and Cu2+ have negative values. The predominating negative values indicate, that in the aquatic environment selfremediation processes have not time to occur, as water is being very active contaminated from the mowings, neighboring agricultural lands.

Для розроблення водоохоронних заходів та забезпечення екологічної безпеки техногенно зумовлених гідроекосистем; що протікають вздовж урбанізованих територій з авіапідприємствами; об’єктом дослідження було обрано техногенно змінену гідроекосистему. Концептуальна модель системи річок складається з річок Нивки та Ірпінь; обидві річки належать до басейну Дніпра; а постійний трофічний зв'язок між ними дозволяє розглядати їх як концептуальну сукупність взаємопов'язаних складових у системі. Основна мета: вивчення особливостей формування техногенно-зумовлених водних екосистем невеликих річок внаслідок антропогенного впливу ремонтних авіапідприємств. Методи: були застосовані методи біотестування та комплексної оцінки класу якості води; модель біологічної трансформації субстрату на основі закону нелінійної математичної моделі Моно та Міхаеліса-Ментена; також було розраховано індекс техногенного впливу кожного полютанта на якість води. Результати: виявлено вміст важких металів; нафтопродуктів; азоту амонійного; азоту нітритного; азоту нітратного в поверхневих водах річок Нивка та Ірпінь. Досліджені проби води з р. Нивки відносяться до V класу якості води; а води р. Ірпінь до IV класу якості. Була показана зміна концентрації забруднюючих речовин в потоці річки Ірпінь. Гідрохімічний аналіз річки показав; що обмежувальні фактори; які впливають на якість води; спричиняють порушення самовідновної здатності водної екосистеми. Обговорення: отримані результати моделювання самовідновлення вод р. Ірпінь свідчать що константа забруднюючих речовин; таких як азот амонійний; азот нітратний; азот нітритний та Cu2 +; має від’ємне значення. Переважання від’ємих значення свідчить про нетрадиційний характер залежності швидкості процесу від концентрації; не встигають відбуватися процеси самоочищення; тому що забруднювачі продовжують досить активно поступати до гідроекосистеми.
Keywords: conceptual model of aquatic ecosystem; Irpin river; technogenic impact index; річка Ірпінь; індекс техногенного впливу; концептуальна модель гідроекосистеми; кафедра екології та екоменеджменту